ANALISIS PRODUKSI DAN POTENSI UNSUR HARA SERASAH DI KAWASAN KONSERVASI MANGROVE PUNTONDO KECAMATAN MANGARABOMBANG KABUPATEN TAKALAR - Asbar Asbar; Muhammad Yunus; Hamsiah Hamsiah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2024)
The study aims to determine the production and potential of litter nutrients of Rhizophora mucronate, as well as estimate the potential of nutrients (C, N, P and K) released into marine waters. Sampling is carried out using the transect-squared method. Mangrove litter avalanches are captured using litter traps and measured in size by filtering litter in water streams connecting mangrove forests and the sea. The potential of mangrove litter nutrient production was analyzed by conducting C, N, P and K nutrient analysis at the Hasanuddin University Chemistry laboratory. The results showed that the dominating mangrove type was R. mucronata. Pontondo mangrove conservation area produces an average litter production of R. mucronata of 3.68 gr/m2/day or 13.41 tons/ha/year of litter; And the biggest contributor is leaves. Rhizhophora mucronata litter potential nutrient production reaches 0.4529 gr-C/m2/day or 1.653 tons-C/ha/year, 0.02904 gr-N/m2/day or 0.1060 tons-N/ha/year, 0.02109 gr-P/m2/day or 0.0770 tons-P/ha/year, and 0.02603 gr-K/m2/day or 0.0950 tons-K/ha/year. Pontondo mangrove conservation forest also contributes litter to marine waters of around 560,832 gr./day of waste to marine waters, and contributes nutrients to marine waters of 69,021.96 gr-C per day; element N of 4,425, 690 gr-N/day; element P is 3,214, 116 gr-P/day and element K is 3,966.515 gr-K/day.